Audit security information on parts of multimedia new based on standards iso 27002: 2005 in radio of the republic of indonesia surabaya - Sejati, Dewangga Putra; tanuwijaya, haryanto; sutomo, erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Pengembangan Media Baru (PMB) is part of information management data used to support the broadcast, such as : save the news will be broadcast, save songs, supporting tasks broadcast in the scope of Radio RRI Surabaya. PMB also collect temporary news from all third class station in East Java and then sent it to first class station at a certain time span. So far, PMB had Confidentiality problems is saving news error that doesn’t match with the planning. The impact of this problem is disruption of the broadcaster to read the news, so that live broadcast become inaccurate. From integrity side is the wholeness of the news coverage results directly accessed was incomplete. The woleness of the news coverage of incomplete results will have an impact on the fall of broadcast event rating and influencing the quality of that event. From availability side, is the delay of provision of information, news, live events, entertainment, and advertising. It can lead to the risk of decrease trust level from listeners and stakeholders RRI Surabaya, and causing losses for RRI Surabaya.Referring to the results of the reviews, surveys, and interviews that have been done, so standard ISO 27002: 2005 is selected. There are three clause assigned is human resources security (Clause 8), the secure area (Clause 9), access control (Clause 11).The result of the calculation process maturity level of audit information security on the PMB RRI Surabaya is 2.55 which is repeatable. That results showed the most of information security process at PMB RRI Surabaya is still in the development stage with limited documentation.